THE IMPORTANCE OF CONTEXT IN TRANSLATION - Akhmedjonova Nigora; Elena E. Deberdeeva (International Journal of Literature and Language Studies, 2026)
Context plays a crucial role in the process of translation, as it determines the meaning, appropriateness, and accuracy of the translated text. This paper explores the significance of context in translation, focusing on linguistic, cultural, and situational aspects. It argues that without proper understanding of context, translation may lead to misinterpretation, loss of meaning, and communicative failure